Development, validation and feasibility study of a remote basic skills assessment for wheelchair service providers. (19th May 2022) - Ardianuari, Satria; Goldberg, Mary; Pearlman, Jonathan; Schmeler, Mark
Abstract: Aim: The purpose of this study was to develop, validate and conduct a feasibility study of three remote basic skills assessment modalities for wheelchair service providers (WSP) including an online case study quiz (m1), an in-person skills assessment (m2) and a video conference skills assessment (m3). Methods: We conducted a literature review; developed and validated 3 basic skills assessments; and conducted a feasibility study of each modality. Results: The literature review revealed that a validated remote basic skills assessment for WSP that reflects all World Health Organization (WHO) 8 wheelchair service provision steps did not exist. We recruited a total of 12 participants for the feasibility study. Two participants dropped out of the study prior to completing a second testing modality. Related to test performance, the results show that our first hypothesis was rejected because only m1 mean score was comparable to the International Society of Wheelchair Professionals (ISWP) Basic Knowledge Test (SD = 0.44). This is in contrast with the Wilcoxon signed-rank test results that show a statistically significant difference between these two modalities. We are therefore not confident that the knowledge test was an appropriate comparison to m1 skills assessment. Hypothesis two was not rejected. The feasibility results reveal 86% success. Conclusion: M1, 2 and 3 have the potential to serve as remote basic skills assessments. However, according to both test performance and feasibility criteria, we believe that m2 has the highest potential to be included in certification processes for basic wheelchair service providers, like the one offered by ISWP. IMPLICATIONS FOR REHABILITATION: A universal remote basic skills assessment that can be accessed across the globe, especially in remote locations where a skilled and experienced provider is not available, is needed. Such test can be an asset to training or professional organisations like ISWP as a way to test WSP competency or to warrant certification. WSP clinical knowledge and skills are essential for the prescription of an appropriate wheelchair to avoid physical harm, abandonment of the device and unnecessary expenses. Properly prescribed wheelchairs allow people with impaired mobility to gain increased ability to perform ADLs, participate in communities, and reduce secondary medical complications such as upper limb repetitive strain injuries, pain, and/or pressure sores.